Panorama : une histoire du design moderne en Belgique = een geschiedenis van modern design in België = a history of modern design in Belgium - Serulus, Katarina; Gimeno Martínez, Javier; ADAM (Museum : Brussels, Belgium) (Bruxelles : CFC-Éditions : ADAM, Brussels Design Museum, 2017)
This book explores the relation between modern design and the Belgian State. The ideology of modern design was closely linked to the utopian attempt of improving the everyday material world. Modernists had the universal belief that everyday spaces and objects affected their users in such a way that design practice could be a kind of political and social reform, or even a moral education. Modern design was however not only invested with these social aspirations, but knew also succes in political circles as an exponent for ideological positions, as a tool for political propaganda or as a marker of national identities. Also the Belgian state mobilized the universal idea of modern design to construct a positive national image for cultural, economic and diplomatic purposes. The famous Expo 58 with its iconic Atomium in Brussels are great examples of this engagement of the state with design to convey a sense of modernity. This book looks beyond the typical Belgian icons and shows how design was framed in economic and political debates in Belgium from the mid 19th century until the 1980s. Exhibition: ADAM Art & Design Atomium Museum, Brussels, Belgium (23.06.2017 - 01.09.2017).
On occasion of the exhibition 'Panorama : a history of modern design in Belgium', held at ADAM, Brussels Design Museum, 23 June 2017 to 7 January 2018.
Parallel texts in French, Dutch and English.
kunstcatalogus
Keywords: Exhibition catalogs; België